Morphology and optical properties of SnO₂ nanofilms - Smyntyna, V.A.; Filevskaya, L.N.; Grinevich, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Results of surface morphology and optical density investigations and the
photoluminescence phenomenon were obtained for SnO₂ thin films. Films having
nanosize of their grains ~ 10-15 nm were obtained using polymeric materials. Evaluation
of a dimensional quantization is fulfilled by two methods: analytically using AFM data,
and by means of optical density spectra; results obtained by these two methods are in a
good agreement.